THE COMMUNITY ASSISTANCE TO INCREASING PREFERENCES OF BROMO-TENGGER AGRO-TOURISM IN EAST JAVA - Dwie Retna Suryaningsih; Moch. Thohiron; Ristani Widya Inti; Nugrahini Susantinah Wisnujati; Rochmad Zulfikar; Ken Sari Nimas Pramhesti (International Journal of Engagement and Empowerment, 2023)
This community service activity aims to provide assistance to the community in Ngadas Village, East Java, with the aim of increasing preference for agro-tourism in the Bromo-Tengger area. Ngadas Village has natural and cultural potential that can be developed as a tourism destination, but the utilization of this potential has not been optimal. Through community service programs, assistance is carried out by facilitating training, workshops, and participatory activities to increase community understanding and skills in developing agro-tourism. Participatory and collaborative approaches are used to involve the community in the planning and development process. It is hoped that through this assistance, the people of Ngadas Village can better understand the potential value of agro-tourism and are able to manage and market it in a sustainable manner. The results of this service are expected to make a positive contribution to improving the local economy and preserving culture in the region